Increased mitochondrial calcium uptake and concomitant mitochondrial activity by presenilin loss promotes mTORC1 signaling to drive neurodegeneration. Issue 10 (9th September 2021) - Ryan, Kerry C.; Ashkavand, Zahra; Sarasija, Shaarika; Laboy, Jocelyn T.; Samarakoon, Rohan; Norman, Kenneth R.
Abstract: Metabolic dysfunction and protein aggregation are common characteristics that occur in age‐related neurodegenerative disease. However, the mechanisms underlying these abnormalities remain poorly understood. We have found that mutations in the gene encoding presenilin in Caenorhabditis elegans, sel ‐ 12, results in elevated mitochondrial activity that drives oxidative stress and neuronal dysfunction. Mutations in the human presenilin genes are the primary cause of familial Alzheimer's disease. Here, we demonstrate that loss of SEL‐12/presenilin results in the hyperactivation of the mTORC1 pathway. This hyperactivation is caused by elevated mitochondrial calcium influx and, likely, the associated increase in mitochondrial activity. Reducing mTORC1 activity improves proteostasis defects and neurodegenerative phenotypes associated with loss of SEL‐12 function. Consistent with high mTORC1 activity, we find that SEL‐12 loss reduces autophagosome formation, and this reduction is prevented by limiting mitochondrial calcium uptake. Moreover, the improvements of proteostasis and neuronal defects in sel ‐ 12 mutants due to mTORC1 inhibition require the induction of autophagy. These results indicate that mTORC1 hyperactivation exacerbates the defects in proteostasis and neuronal function in sel ‐ 12 mutants and demonstrate a critical role of presenilin in promoting neuronal health. Abstract : Proteostasis decline is a common feature in age‐related disease. Loss of SEL‐12/presenilin function leads to increased calcium transfer from the endoplasmic reticulum to the mitochondria resulting in mitochondrial hyperactivity. The mitochondrial hyperactivity promotes mTORC1 signaling that deregulates proteostasis by inhibiting autophagy, which ultimately impairs neuronal fitness.